Green marketing today - a mix of trust, consumer participation and life cycle thinking = Green marketing dzisiaj - połączenie zaufania, zaangażowania konsumenta i myślenia kategoriami cyklu życia - Lewandowska, Anna; Witczak, Joanna; Kurczewski, Przemysław (Zielona Góra: Faculty of Economics and Management Press)
A transition for a green, circular economy has encouraged companies to use new tools which boost sustainability. The purpose of this article is to discuss the consideration of life cycle thinking in green marketing as realized by companies. This theoretical-conceptual study aims to analyze life cycle assessment (LCA) as a useful tool for assessing green marketing goals.
Keywords: zielony marketing; komunikacja środowiskowa; LCA; środowiskowa ocena cyklu życia; green marketing; environmental communication; life cycle assessment (LCA)